Effects of Antipsychotics on Dentate Gyrus Stem Cell Proliferation and Survival in Animal Models: A Critical Update. (24th October 2012) - Keilhoff, Gerburg; Fusar-Poli, Paolo; Becker, Axel
Abstract : Schizophrenia is a complex psychiatric disorder. Although a number of different hypotheses have been developed to explain its aetiopathogenesis, we are far from understanding it. There is clinical and experimental evidence indicating that neurodevelopmental factors play a major role. Disturbances in neurodevelopment might result in alterations of neuroanatomy and neurochemistry, leading to the typical symptoms observed in schizophrenia. The present paper will critically address the neurodevelopmental models underlying schizophrenia by discussing the effects of typical and atypical antipsychotics in animal models. We will specifically discuss the vitamin D deficiency model, the poly I:C model, the ketamine model, and the postnatal ventral hippocampal lesion model, all of which reflect core neurodevelopmental issues underlying schizophrenia onset.